Pelatihan Penulisan Book Chapter untuk Penguatan Literasi Akademik Guru PAUD di Kabupaten Tapanuli Utara - Lince Rauli Ture; Lasmaria Nami Simanungkalit (Penerbit Widina, Widina Media Utama, 2025)
The limited academic literacy of Early Childhood Education (ECE) teachers, particularly in writing scholarly works in accordance with educational standards, remains a challenge in the context of continuous professional development. This community service activity aimed at improving the academic literacy of early childhood education (PAUD) teachers through a book chapter writing training program. The implementation method employed a structured integration of training and mentoring activities, including lectures, discussions, writing practice, and intensive, ongoing guidance. The participants consisted of 14 early childhood education (PAUD) teachers who attended the entire series of activities, from the preparation stage through to the evaluation phase. The results of the activity showed an improvement in participants’ understanding of the structure and organization of book chapter writing, the principles of academic writing, as well as citation techniques and reference management. The findings revealed that 11 participants (80%) were able to complete initial drafts of book chapters aligned with the assigned themes. Participants also showed increased motivation and confidence in academic writing. Overall, the program proved effective in enhancing the academic literacy of early childhood education teachers and supporting sustainable professional development through scientific publication.ABSTRAKKeterbatasan literasi akademik guru Pendidikan Anak Usia Dini (PAUD), khususnya dalam penulisan karya ilmiah yang sesuai dengan kaidah akademik, masih menjadi tantangan dalam pengembangan profesional berkelanjutan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan literasi akademik guru PAUD melalui pelatihan penulisan book chapter. Metode pelaksanaan mengombinasikan pelatihan dan pendampingan secara terstruktur melalui ceramah, diskusi, praktik menulis, serta bimbingan intensif dan berkelanjutan. Peserta kegiatan berjumlah 14 guru PAUD yang mengikuti seluruh rangkaian kegiatan mulai dari tahap persiapan hingga evaluasi. Hasil kegiatan menunjukkan peningkatan pemahaman peserta terhadap struktur dan sistematika penulisan book chapter, prinsip penulisan ilmiah, serta teknik sitasi dan pengelolaan referensi. Hasil penelitian ini menjelaskan bahwa 11 peserta (80%) berhasil menyusun draf awal book chapter sesuai dengan tema yang ditentukan. Seluruh peserta menunjukkan peningkatan motivasi dan kepercayaan diri dalam menulis karya ilmiah. Kegiatan ini disimpulkan efektif dalam memperkuat literasi akademik guru PAUD serta berpotensi mendorong produktivitas publikasi ilmiah sebagai bagian dari pengembangan profesional berkelanjutan.